ANALISIS PENGARUH PLACE, PROMOTION, DAN PEOPLE TERHADAP KEPUTUSAN KONSUMEN MELAKUKAN PEMBELIAN PRODUK PASAR MODAL DENGAN MENGGUNAKAN JASA EQUITY BROKERAGE DI PT SUCORINVERS CENTRAL GANI CABANG KEDIRI - Ernestivita, Gesty (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2016)
Competition in the business world at this time is very tight, not just goods, services products also can not be separated from marketing. Marketing has become a very important subject in everyday life in line with the development of the economy. This study aims to analyze the influence of Place, Promotion and People of the consumer's decision to purchase Equity Brokerage services in PT Sucorinvest Central Gani Kediri either partially or simultaneously. Research variables used are Place, Promotion, People and purchasing decisions. The population in this study are 158 respondents. Samples were determined using purposive sampling number of 35 respondents using characteristics. Data were collected using questionnaires, then analyzed using multiple linear analysis, which is processed with SPSS XVI. The research proves that simultaneous variable Place, Promotion and People positive and significant impact on the purchase decision variable coefficient F count = 4,037> F table (2.88). The results also prove that the variables place positive effect but not significant with a coefficient of 1.820 thitung, Promotion and People variable positive and significant influence on purchasing decisions, with a coefficient of 3.014 and 3.895 tcount Promotion for People variables while ttable amounted to 1,891. Keywords: Marketing Mix, Place, Promotion, People, Buying Decision